Detection of Brucella Species from Serum And Aborted Materials and Differentiation of Vaccine from Field Strain by Polymerase Chain Reaction in Buffaloes - Islam, M. R.; Filia, G.; Gupta, M. P. (The Indian Journal of Animal Reproduction, 2021)
The present study was aimed to assess the suitability of polymerase Chain Reaction  (PCR) for detection of Brucella species from serum and aborted materials along  with the differentiation of vaccinated animals from the animals infected with  field strains. The samples collected included nine abomasal contents of the  aborted foetus and 178 sera samples. All the samples were processed and DNA  was extracted for detection and differentiation of Brucella strains. PCR detected  amplicons of 193-bp in 6 (66.66%) samples of aborted fetuses and 68 (38.20%)  sera samples. In all the six positive fetal stomach contents, Brucella abortus (B.  abortus) was detected. However, serum samples positive for Brucella genus PCR,  failed to yield positive results in species specific PCR. DNA from six B. abortus positive samples when subjected to Bruce ladder PCR resulted in amplification of  five fragments of 1682, 794, 587, 450 and 152 bp in size. However, B. abortus S-19  DNA did not produce 587 bp fragment common to Brucella strains tested. Keeping  in view, the challenges associated with conventional assays and isolation of agent,  molecular methods especially PCR is a sensitive, specific and robust alternative  in achieving an accurate diagnosis and differentiation of the agent especially in  animals, in which this disease has an obscure nature.
Keywords: Brucellosis; Buffaloes; PCR; Vaccine; Field strains